2018
DOI: 10.1542/hpeds.2017-0109
|View full text |Cite
|
Sign up to set email alerts
|

Potential Opportunities for Prevention or Earlier Diagnosis of Child Physical Abuse in the Inpatient Setting

Abstract: Infants hospitalized with perinatal-related conditions, symptoms concerning for occult AHT, and injuries are inpatient populations who may benefit from abuse prevention efforts and/or risk assessments. Head injuries and symptoms concerning for occult AHT (eg, isolated vomiting, seizures, and brief resolved unexplained events) may represent missed opportunities to diagnose AHT in the inpatient setting; however, this requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…Hospitalizations qualified as being abuse related if they met any of the following criteria: (1) ICD-9-CM codes for an injury and abuse, (2) ICD-9-CM codes for an injury and assault, (3) ICD-9-CM codes for retinal hemorrhages or anoxic brain injury and abuse, or (4) any ICD-9-CM code for abusive head trauma (Supplemental Table 4). 3,[28][29][30]…”
Section: Outcome Measurementioning
confidence: 99%
See 1 more Smart Citation
“…Hospitalizations qualified as being abuse related if they met any of the following criteria: (1) ICD-9-CM codes for an injury and abuse, (2) ICD-9-CM codes for an injury and assault, (3) ICD-9-CM codes for retinal hemorrhages or anoxic brain injury and abuse, or (4) any ICD-9-CM code for abusive head trauma (Supplemental Table 4). 3,[28][29][30]…”
Section: Outcome Measurementioning
confidence: 99%
“…However, the first 6 months of an infant's life is a period with high rates of abuse and abuse-related fatality. 3,30 Second, the NRDs did not allow for an assessment of individual, family, and community psychosocial contributors to abuse risk, such as maternal educational attainment, marital status, or caregiver mental illness. 48 Third, we could not control for social and preventive interventions that some newborns would have almost certainly received.…”
Section: Figurementioning
confidence: 99%
“…However, research demonstrates that instances of abuse and neglect are often not identified by pediatricians ( Hymel et al, 2018 ; Jenny et al, 1999 ; Lane et al, 2002 ). Notably, prior work suggests that certain injuries are more common among children who are eventually diagnosed with maltreatment ( Lindberg et al, 2015 ; Puls et al, 2018 ; Sheets et al, 2013 ; Thackeray et al, 2016 ). Specifically, one study examined infants less than 12 months of age with definite abuse and found that more than one-fourth (28%) had a previous injury suggestive of maltreatment (i.e., a sentinel injury).…”
Section: Introductionmentioning
confidence: 99%
“… Thackeray et al (2016) determined that children less than 12 months of age with an abuse diagnosis or a skeletal survey, which often indicates provider concern for abuse, contusions (28%), fractures (27%), open wounds (17%), and superficial injuries (12%) were relatively common. In a study of inpatient pediatric hospitalizations, children who were diagnosed with physical abuse were more likely to have previous diagnoses of fractures, head injuries, and symptoms concerning for abusive head trauma than children with unintentional injuries ( Puls et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation